The integration of groundwater protection into land-use planning, certification and standardization of quality of urban supply systems. (2017) - Jiménez-Madrid, Alberto; Martínez-Navarrete, Carlos; Jiménez-Fernández, Pedro
Abstract: Groundwater is an essential resource for water supply. For this reason, it is necessary to integrate and harmonise efforts to protect groundwater quality with socio-economic activities and existing land-use patterns in any given region, as well as complying with the requirements of the EU Water Framework Directive. In addition, land management seeks to coordinate and harmonise policies with regional impacts. Water—as a public good and an essential resource for the development of life and the evolution of populations—needs to become one of the main pillars of management for a variety of regional policies. Therefore, water resources planning does not make sense without firstly considering forecasted land management patterns. The objective of this work is to standardize the process of managing the supply systems and prove their quality by certification. This will require guaranteeing the sustainable management and obtaining the certificate. During this long process, there may be complications that prevent achievement of the ultimate objective. For this, it is necessary to promote a standardization tool, which will value the efforts of the various agencies involved in the protection and management of groundwater used for human consumption in achieving sustainable management of water resources.